ANALISIS PERSEPSI ANAK TERHADAP GAYA PENGASUHAN ORANGTUA, KECERDASAN EMOSIONAL, AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS XI DI SMA NEGERI 3 SUKABUMI - Riza Arisandi; Melly Latifah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
The study aimed to analyze child’s perception on parenting style, level of emotional intelligence and academic achievement of high school students at SMA 3 Sukabumi. Results showed that more than 60 percent student perceived that parenting style is classified as emotional coach. In general level of EQ of the students classified as moderate (62.8%) while the rest classified as high. There was significant difference in term of duration of student activities based on classes (IPA or IPS) while by gender there was not significance. Academic achievement of girls was significantly higher than boys, also their motor achievement. Parenting style of the parent was significantly correlated with EQ of student, particularly in term of emotional awareness, self motivation, social relationship, and total EQ. In line with this total EQ and social relationship have positive and significant correlation with cognitive achievement, while empathy, social relationship and total EQ also have significant associations with motor achievement. Only self motivation was significantly related to attitude of students.